2022
DOI: 10.1039/d2ta01967a
|View full text |Cite
|
Sign up to set email alerts
|

Type-II Weyl fermion induced hydrogen adsorption in a two-dimensional electride [Ca2N]+·e

Abstract: Electrides, in which excess electrons are weakly bounded by lattice interstitial position, are suitable for achieving topological states. The topological properties of electrides give rise to a boost to their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…In other words, the energy window of the surface state passing through the Fermi level is closely related to the Gibbs free energy. This result has also been confirmed in other materials such as PtGa 33 and electride Ca 2 N. 52…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In other words, the energy window of the surface state passing through the Fermi level is closely related to the Gibbs free energy. This result has also been confirmed in other materials such as PtGa 33 and electride Ca 2 N. 52…”
Section: Resultssupporting
confidence: 73%
“…In other words, the energy window of the surface state passing through the Fermi level is closely related to the Gibbs free energy. This result has also been confirmed in other materials such as PtGa 33 and electride Ca 2 N. 52 Subsequently, we applied À5% to 5% strains along the k z direction for the Mg 3 Bi 2 compound. The finding is that the crossing point (P) is extremely insensitive to strain, as shown in Fig.…”
Section: Catalytic Performancesupporting
confidence: 78%
“…The last few years have seen research in this field with a focus on developing efficient topological material catalysts for hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and reduction. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] To date, the topological catalyst has become a new frontier in both chemistry and materials science.…”
Section: Comentioning
confidence: 99%
“…Quantum catalysis theory is a novel catalyst design theory developed in the last decade, which has been validated by several comparisons of theorical and experimental results. Chen et al proposed for the first time that the surface states of a topological insulator can diffuse to surface-supported Au clusters to promote CO oxidation . Later, it was found that a few classified topological semimetallic materials can also be used as catalysts for certain reactions, such as the Weyl semimetals (WSMs) NbAs and TaAs for simple molecule activation reactions and the topological nodal line semimetals (TNLSMs) ZrSiS and ZrSiSe for the HER .…”
Section: Introductionmentioning
confidence: 99%